Litigation to Access Health Services: Ally or Enemy of Global Public Health? - Alexandre Martins; Sydney Allen (Ubiquity Press, 2020)
Background: Some scholars and global health advocates argue that litigation is a strategy to advance public health care, especially in those countries that do not have specific legislation to guarantee access to basic health care services. However, strategic litigation has another side, known as judicialization of the right to health, particularly present in the Latin American region where most countries incorporate the right to health into their constitutions, but their citizens still struggle with health disparities. Objectives: Considering these two perspectives on litigation in health care, this paper examines the phenomenon of litigation in health care and its impact on public health in Brazil, where there is an ambiguous process of litigation in health care. Methods: Comparing the literature of both the use of strategic litigation for advancing public health and the judicialization of the right to health, this paper develops an ethical analysis of the impacts of strategic litigation for individuals and societies, using Brazil's public health care system and its policies as case-study of the impact of court decisions on the management of the system. Findings: Supporters of strategic litigation present experiences in African countries using this strategy to access a specific medical service led to enforce the creation of health-related policies by authorities and policymakers. However, in Brazil, a country with the right to health guaranteed by its Constitution, strategic litigation creates access to health care for some individuals, but also results in complex sociomedical challenges with significant impact for public administration and distributive justice. Conclusions: Strategic litigation can lead to ambiguous results, which will depend on the local context and the existence or not of public health services and health-related policies. When this strategy is considered, ethical analysis helps to understand how litigation can both benefit and damage individuals' health and the public health system in the complex context and diverse reality of Brazil. As a result, strategic litigation must be considered from an ethical perspective of prudence and discernment in a close interaction with the local reality, its particular circumstances, culture, policies, and laws.